2021
DOI: 10.1039/d1ta02326h
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of graphene mesosponge via catalytic methane decomposition on magnesium oxide

Abstract: MgO has specific catalysis for CH4-to-C conversion, and functions as a cost-effective and environmentally friendly template to produce graphene mesosponge with developed porosity, excellent stability, and super soft and elastic properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 43 publications
1
53
0
Order By: Relevance
“…The resultant Lewis acidbase pair at oxygen vacancies can make the formation of singlewalled NPG kinetically feasible with a signicantly lower activation energy as compared to a radical mechanism. 24 Interestingly, further desorption of H 2 O from the g-ANP surfaces by heating from 900 to 1000 C resulted in slower reaction rates (Table S1 †). This could be explained by the structural changes of g-ANP: The specic surface area of g-ANPs decreased from 158 m 2 g À1 for pristine to 139 m 2 g À1 upon treatment at 900 C for 2 h, and eventually decreased to 124 m 2 g À1 upon annealing at 1000 C for 2 h. The structural reorganization during CH 4 -CVD was also supported by 27 Al nuclear magnetic resonance (NMR), which showed an increase in octahedrally coordinated stable Al centers ( [6] Al) induced by annealing during CH 4 -CVD (Fig.…”
Section: Dft Calculationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The resultant Lewis acidbase pair at oxygen vacancies can make the formation of singlewalled NPG kinetically feasible with a signicantly lower activation energy as compared to a radical mechanism. 24 Interestingly, further desorption of H 2 O from the g-ANP surfaces by heating from 900 to 1000 C resulted in slower reaction rates (Table S1 †). This could be explained by the structural changes of g-ANP: The specic surface area of g-ANPs decreased from 158 m 2 g À1 for pristine to 139 m 2 g À1 upon treatment at 900 C for 2 h, and eventually decreased to 124 m 2 g À1 upon annealing at 1000 C for 2 h. The structural reorganization during CH 4 -CVD was also supported by 27 Al nuclear magnetic resonance (NMR), which showed an increase in octahedrally coordinated stable Al centers ( [6] Al) induced by annealing during CH 4 -CVD (Fig.…”
Section: Dft Calculationsmentioning
confidence: 99%
“…[3][4][5] In contrast, the synthesis of a three-dimensionally and periodically arranged single-walled graphene with a negative curvature has remained a challenge since Mackay and Terrones proposed an ideal 3D minimumsurface graphene structure (Scheme 1) in 1991, 6 despite the recent advances in organic synthesis realizing small molecules with a few heptagons 7,8 or octagons. 9,10 In this regard, chemical vapor deposition (CVD) on templated materials [11][12][13][14][15][16][17][18][19][20][21][22][23][24] is a prominent strategy for realizing 3D minimum-surface graphene. Especially, CVD on alumina nanoparticles (ANPs) that display high thermal stability 25 as the templates gave nanoporous graphene (NPG) materials from CH 4.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…36 Such porous OCFs can be considered as a kind of graphene-based nanoporous material, which is an analogue of ZTC and graphene mesosponge (GMS). 13,21,22,24,126 We have previously revealed that the single-graphene frameworks of ZTC and GMS make them extraordinarily flexible despite their small pore size (o10 nm). Such nanoporous flexible materials function as an elastic nanosponge, leading to a new phenomenon of force-responsive phase transitions.…”
Section: Force-responsive Propertiesmentioning
confidence: 99%
“…More recently, the hard-template method has been expanded to the synthesis of graphene-based 3D nanoporous materials using Ni-foam, 20 Al 2 O 3 and MgO nanoparticles. [21][22][23][24] In contrast to the hard-template method, a soft-template method was developed around the 2000s, and ordered mesoporous carbons have been fabricated from block copolymers, 25 and from the mixture of thermosetting polymer and surfactant micelles. 26,27 The history of templating techniques has been summarized in some review papers, 13,28 and we avoid overlapping of their content in this article.…”
Section: Introductionmentioning
confidence: 99%